2015
DOI: 10.1002/ar.23197
|View full text |Cite
|
Sign up to set email alerts
|

No Sexual Dimorphism Detected in Digit Ratios of the Fire Salamander (Salamandra salamandra)

Abstract: It has been proposed that digit ratio may be used as a biomarker of early developmental effects. Specifically, the second-to-fourth digit ratio (2D:4D) has been linked to the effects of sex hormones and their receptor genes, but other digit ratios have also been investigated. Across taxa, patterns of sexual dimorphism in digit ratios are ambiguous and a scarcity of studies in basal tetrapods makes it difficult to understand how ratios have evolved. Here, we focus on examining sex differences in digit ratios (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 73 publications
(160 reference statements)
4
15
0
Order By: Relevance
“…Our sample size represents an exhaustive search for adults for about 3 months that resulted in frequent recaptures suggesting we had sampled the majority of active adults. Although our sample size for cane toads is much smaller than our t ungara frog sample, it is similar to those of other studies examining sexual differences digit ratios (Balogov a et al, 2015). Adults were recognized as individuals larger than 9 cm following Zug and Zug (1979).…”
Section: Study Species and Digit Measurementssupporting
confidence: 74%
See 1 more Smart Citation
“…Our sample size represents an exhaustive search for adults for about 3 months that resulted in frequent recaptures suggesting we had sampled the majority of active adults. Although our sample size for cane toads is much smaller than our t ungara frog sample, it is similar to those of other studies examining sexual differences digit ratios (Balogov a et al, 2015). Adults were recognized as individuals larger than 9 cm following Zug and Zug (1979).…”
Section: Study Species and Digit Measurementssupporting
confidence: 74%
“…In two species of anurans, males exhibit a larger digit ratio than females (Chang, 2008, Direnzo andStynoski, 2012), while there is no difference between the sexes in a third species (Germano et al, 2011). Two recent studies on five species of caudates found convincing evidence that females had larger digit ratios than males in one species, but found inconsistent or no sex-biased pattern in the digit ratios in four other species (Balogov a et al, 2015;Kaczmarski et al, 2015).…”
mentioning
confidence: 99%
“…Hands and feet, respectively, were placed dorsal side up on an ocular micrometer and enclosed by a second glass slide to obtain straightened digits without compression (Balogová et al, ). Digital photographs were taken with a Canon EOS 550D DSLR with an attached EF‐S 60 mm Macro lens from a fixed distance.…”
Section: Methodsmentioning
confidence: 99%
“…In spite of the high morphological diversity observed at the intraspecific level, there is a limited number of morphological studies on this species, most of which are focused on coloration (Bosch and López‐Bueis, ; Pasmans and Keller, ; Balogová and Uhrin, ; Beukema et al, ). Some studies have also explored sexual dimorphism in size (Degani, ; Cordero‐Rivera et al, ; Balogová et al, ) and shape (Labus et al, ), showing that, as in many other urodeles, females are the larger sex, with relatively larger heads, interlimb distances and parotid glands while males have longer limbs and feet (Labus et al, ; Reinhard et al, ). However, although snout shape has been considered as a key trait to identify sexual dimorphism (Labus et al, ) and to distinguish between subspecies in S. salamandra (Bas and Gasser, ; Velo‐Antón and Buckley, ) head shape variation has been poorly studied.…”
Section: Methodsmentioning
confidence: 99%